2013
DOI: 10.1590/s1984-29612013000200038
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transmission of Anaplasma marginale in beef cattle chronically infected in southern Brazil

Abstract: In this study, we have investigated the incidence of transplacental transmission of Anaplasma marginale in chronically infected cows with no history of acute anaplasmosis during gestation. In addition, we evaluated various techniques for detection of transplacental transmission of A. marginale. Blood samples were collected from 30 cows at three different periods: at the time of artificial insemination, at gestational diagnosis, and after calving. Also, blood was collected from the newborn calves, including one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…In our study, a high transplacental transmission rate of A. marginale was observed. This result has been reported in most acute experimental infections (Zaugg, 1985;Ribeiro et al, 1995;Kessler, 2001), and also in naturally infected pregnant cows (Norton et al, 1983;Ribeiro et al, 1995;Maldonado et al, 2012;Grau et al, 2013;Silva et al, 2015). Prior studies have demonstrated that transmission occurs in the second and third trimesters of pregnancy (Zaugg and Kuttler, 1984;Zaugg, 1985;Potgieter and Van Rensburg, 1987;Ribeiro et al, 1995).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In our study, a high transplacental transmission rate of A. marginale was observed. This result has been reported in most acute experimental infections (Zaugg, 1985;Ribeiro et al, 1995;Kessler, 2001), and also in naturally infected pregnant cows (Norton et al, 1983;Ribeiro et al, 1995;Maldonado et al, 2012;Grau et al, 2013;Silva et al, 2015). Prior studies have demonstrated that transmission occurs in the second and third trimesters of pregnancy (Zaugg and Kuttler, 1984;Zaugg, 1985;Potgieter and Van Rensburg, 1987;Ribeiro et al, 1995).…”
Section: Discussionsupporting
confidence: 57%
“…Two of these animals also had leptospiraemia, with a co-infection of A. marginale, BVDV and Leptospira sp., which may have acted synergistically to decrease the haematocrit levels and lead to death. The other calf had a presumptive diagnosis of fatal neonatal anaplasmosis Previous reports of congenital and asymptomatic babesiosis (for B. bovis) and anaplasmosis (Fowler and Swift, 1975;Zaugg, 1985;Osaki et al, 2002;Maldonado et al, 2012;Grau et al, 2013;Santarosa et al, 2013), or sick calves with anaplasmosis and babesiosis (De Vos et al, 1976;Paine and Miller, 1977;Norton et al, 1983;Passos and Lima, 1984;Barbosa et al, 1994;Bracarense et al, 2001;Yeruham et al, 2003) have been published. Thus, it is evident that this pathway is important in some regions (Silva et al, 2015) for the ease of transmission, and as a cause of economic loss that it might entail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2.32 × 10 -3 ) in the uterus of co-infected non-pregnant bitches in this study. The possibility of vertical transmission of A. platys in dogs is in agreement with knowledge of this event occurring for Anaplasma marginale and Anaplasma phagocytophilum in cattle [ 31 , 32 ], whereas the minimal data relative to in utero transmission of A. phagocytophilum in dogs [ 33 ] did not support transplacental transmission. Controlled laboratory studies involving puppies from bitches infected with A. platys should be addressed to better understand this transmission pattern.…”
Section: Discussionsupporting
confidence: 78%
“…Anaplasma marginale is an obligate intracellular bacterium. It can be biologically transmitted by ticks, and mechanically transmitted by hematophagous dipterans, infected blood in photites, and also transplacental (Aubry & Geale 2011, Grau et al 2013. This rickettsia causes a condition called anaplasmosis, which is endemic in tropical and subtropical areas, and result in considerable economic loses for the beef and dairy industries worldwide (Kocan et al 2015).…”
Section: Introductionmentioning
confidence: 99%